Optimasi Waktu Produksi Metabolit Sekunder dan Skrining Aktivitas Antibakteri Isolat Actinomycetes Rizosfer Tanaman Tin (Ficus carica) - Warsi, Warsi; Sulistyani, Nanik (Jurnal Teknologi Laboratorium, 2018)
Some Actinomycetes isolates of a tin plant (Ficus carica L.) have been obtained, namely T24M, T18, T19, T24, T25, T34, T37, T41, and T43. The aim of this study was to optimize the production of secondary metabolites (antibiotics) and screening antibacterial activity against Methicillin-Resistant Staphylococcus aureus (MRSA) from the Actinomycetes isolate of the tin rhizosphere. The study was performed with test an activity of the culture fluid from Actinomycetes isolate against MRSA by the well method. The result of optimization secondary metabolite production showed that the second day was the best incubation time to harvest antibiotics. The results showed that bacterial isolates of T24M produced antibiotics that could inhibit MRSA growth.